Detection of rtN236T mutation associated with adefovir dipivoxil resistance in Hepatitis B infected patients with YMDD mutations in Tehran - Monavari, Seyed Hamidreza (Tehran University of Medical Sciences, 2013)
BACKGROUND OBJECTIVES: The risk of adefovir dipivoxil resistance emergence has increased in lamivudine-resistant hepatitis B infected patients. The mutations known as causing adefovir resistance, rtN236T and rtA181V/T, are detected within the D and B functional domain of the HBV polymerase, respectively. In this study, we intended to determine the pre-existing adefovir-resistance mutations in patients infected with LAM resistant mutants prior to starting adefovir therapy. MATERIAL AND METHODS: The study included 30 patients with chronic hepatitis B with lamivudine resistance mutations in the YMDD motif that experienced viral breakthrough. RESULTS: After alignment of protein coding sequences, the rtN236T mutation was observed in two (6.6%) patients, while twenty-eight others had neither rtN236T, nor rtA181V/T mutation. All 30 patients were infected with genotype D of hepatitis B virus. CONCLUSIONS: The early detection of LAM-resistance mutations may allow a timely chance of therapy to avoid hepatitis flare-up. This data suggests that monitoring of ADV-resistance mutations in ADV naïve patients can be considered in selecting the appropriate anti-viral regimen.